Type I Diabetes—A Rare Adverse Event Described in Patients Receiving Immunotherapy Versus a Side Effect from SARS-CoV-2 Infection - Raluca-Ileana Pătru; Miruna Ghigeanu; Maria-Alexandra Barbu; Andreea Iuliana Ionescu; Antone-Iordache Ionuț-Lucian (Reports)
Background and Clinical Significance: Lung cancer, a leading cause of global cancer diagnoses, maintains the highest mortality risk despite advances in treatment. Immunotherapy agents, such as anti-programmed death-1/programmed death ligand-1 (PD-1/PD-L1), have revolutionized care for non-small cell lung cancer (NSCLC). However, the success is tempered by the emergence of immune-mediated adverse reactions, including the rare onset of type I diabetes. The incidence of diabetes mellitus increased during the SARS-CoV-2 pandemic. While there are several cases of new-onset diabetes after COVID-19 and COVID-19 vaccination, no case of new-onset type 1 diabetes after COVID-19 was described in an immune checkpoint inhibitor (ICI)-treated patient. Case Presentation: A 57-year-old male with stage IV NSCLC (brain and liver metastases) who had been treated with nivolumab for 4 years appeared positive for SARS-CoV-2 infection at a routine check. After two weeks, he was admitted to our clinic with severe fatigue, hyperglycemia, hyponatremia, and hyperkalemia. HbA1c level was normal and serum peptide C was undetectable. Nivolumab treatment was ceased, and the patient became fully dependent on basal–bolus insulin. After 3 months, the patient showed a complete imagistic remission. Conclusions: The case presented significant challenges due to the unclear etiology of newly onset diabetes and the uncommon age at which type 1 diabetes is developed. The outcome suggests that anti-PD-1 and SARS-CoV-2 infection can act synergistically.